Pengaruh Korupsi Pajak Dan Keadilan Pajak Terhadap Kepatuhan Wajib Pajak Di KP2KP Pariaman - Defika, Della; EDT, Risa Wahyuni; Dewi, Winona Kumara (Universitas Sumatera Barat, 2022)
This research aims to determine the influence of tax corruption and tax justice on taxpayer compliance at the Pariaman Tax Counseling and Consultation Services Office (KP2KP). This type of research is quantitative research. The sample in this research consisted of 100 taxpayers. The data collection technique uses a questionnaire, while the data analysis method uses validity and reliability tests, descriptive statistics, classical assumptions, multiple linear regression analysis, and statistical tests. The results of the research show that the tax corruption variable has a significant effect on taxpayer compliance. The tax justice variable has a significant effect on taxpayer compliance. The tax corruption and tax justice variables simultaneously have a significant effect on the dependent variable of taxpayer compliance.